Drying behavior and permeability of Eucalyptus Grandis Lumber - Jankowsky, Ivaldo P.; V. dos Santos, Gilson Roberto (Maderas. Ciencia y Tecnología, 2014)
In memoriam of Dr. H. Peter STEINHAGEN Although the increasing economic importance of Eucalyptus lumber to furniture and other value added products manufacturing, its industrial use is still small. One of the main reasons is the difficulty to dry the lumber and related loses of row material. There is a general recommendation in literature to use a low drying rate in initial stages of the process, and changing to a more aggressive drying after removal of liquid water from the lumber. According classical theory about drying of porous material, this point should coincide with the predominance of diffusion phenomena in the moisture movement; which could be determined through the characteristic drying curve of the material. With the objective to get better knowledge about the drying of Eucalyptus grandis lumber, its characteristic drying curve was determined, and the results proved that Eucalyptus grandis lumber is not permeable to liquid flow. Based on its characteristic drying curve, it is possible to suggest the change of drying conditions when lumber moisture content, dry basis, is between 35% and 40%, then starting a more aggressive drying.